Injection of gaseous hydrogen into a natural gas pipeline. (19th July 2022) - Eames, I.; Austin, M.; Wojcik, A.
Abstract: The injection of pure hydrogen at a T -junction into a horizontal pipe carrying natural gas is analysed computationally to understand the influence of blending and pipe geometry (diameter ratio, various 90 ° orientations) on mixing, for a target of 4.8–20% volume fraction hydrogen blend. The strongly inhomogeneous distribution of hydrogen within the pipe flow and on the pipe walls could indicate the location of potential pipe material degradation including embrittlement effects. The low molecular mass of hydrogen reduces the penetration of a side-branch flow and increases the buoyancy forces leading to stratification with high hydrogen concentrations on the upper pipe surface, downstream of the branch. Top-side injection leads to the hydrogen concentration remaining > 40 % for up to 8 pipe diameters from the injection point for volumetric dilutions ( D ) less than 30%. Under-side injection promotes mixing within the flow interior and reduces wall concentration at the lower surface, compared to top-side injection. The practical implications for these results, in terms of mixing requirements and the contrasting constraint of codes of practice and energy demands, are discussed. Highlights: Injection of hydrogen through a T junction leads to poor mixing and high concentrations of hydrogen on pipe walls. Stratification leads to higher hydrogen concentration near upper pipe wall. Higher hydrogen concentration on walls leads to the embrittlement of high-tensile steels. ASME B31.3 indicates that gas pressure needs to be decreased which contrasts with the energy flux constraint.